Opportunities and Challenges in the Sustainable Development of Lumpue Beach, Parepare City, South Sulawesi - Yusuf, Muhammad; Jamaluddin, Muhammad Arya (PINISI Discretion Review, 2025)
This study investigates the development strategies for Lumpue Beach in Parepare City, identifying key business opportunities and management challenges. Employing a qualitative approach, this applied research utilizes field observations, in-depth interviews, and documentary analysis. The findings indicate that the effective development of Lumpue Beach necessitates proactive engagement from the local government, particularly through the establishment of a dedicated management institution. Such a strategy is crucial for creating a structured and sustainable governance framework. Significant business opportunities exist in the culinary sector, tourism services, recreational equipment rentals, and the local creative economy. However, the area's development is impeded by several challenges, including inadequate infrastructure, insufficient tourism promotion, and limited community participation in the management process. This research provides strategic recommendations for governmental bodies and stakeholders to optimize the tourism potential of Lumpue Beach, positioning it as a premier destination capable of fostering inclusive and sustainable local economic growth.